2019
DOI: 10.1002/ece3.5022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of nodule worm in a community of Bornean primates

Abstract: Strongyles are commonly reported parasites in studies of primate parasite biodiversity. Among them, nodule worm species are often overlooked as a serious concern despite having been observed to cause serious disease in nonhuman primates and humans. In this study, we investigated whether strongyles found in Bornean primates are the nodule worm Oesophagostomum spp., and to what extent these parasites are shared among members of the community. To test this, we propose two hypotheses that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 62 publications
1
12
2
Order By: Relevance
“…However, in our study we used ITS sequences to discriminate nematode species as the ITS regions are among the most variable nuclear loci, with a sufficient number of comparative sequences in databases. Our result demonstrated the same phylogenetic similarity observed from Frias et al 38 . Accordingly, the rapid mode of ITS evolution including frequent indels makes alignment of ITS haplotypes more challenging compared to protein-coding markers, which can adversely affect the reliability of phylogenetic reconstruction 42 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, in our study we used ITS sequences to discriminate nematode species as the ITS regions are among the most variable nuclear loci, with a sufficient number of comparative sequences in databases. Our result demonstrated the same phylogenetic similarity observed from Frias et al 38 . Accordingly, the rapid mode of ITS evolution including frequent indels makes alignment of ITS haplotypes more challenging compared to protein-coding markers, which can adversely affect the reliability of phylogenetic reconstruction 42 .…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondrial and nuclear genes are used in phylogenetic studies on strongylid species 41 . Based on the mitochondrial cox1 gene, Frias et al 38 showed that Bornean primates are subject to O. aculeatum infection. However, in our study we used ITS sequences to discriminate nematode species as the ITS regions are among the most variable nuclear loci, with a sufficient number of comparative sequences in databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of concern are soil-transmitted helminths (STHs) whose partial development outside their hosts allows persistence of infective stages in the environment, enabling transmission between closely related host species Cibot et al, 2015). Several studies have described cases of zoonotic STHs transmission in sympatric populations of NHPs and humans (Cibot et al, 2015;Frias et al, 2019). However, little is known about urban zoonoses and possible reservoir hosts despite having abundant wildlife in most urban habitats in Africa.…”
Section: Introductionmentioning
confidence: 99%